API AND UI FOR TABLE LOOKUP APPROACH STEMMING ALGORITHM - P, Jennifer .; Muthukuavel, A. (International Journal of Psychosocial Rehabilitation, 2020)
The system to retrieve the needed information or data from the google library or from the system library is completely depended on the technique which is called Information retrieval system. The proposed technique here, it retrieves the information on the supported text document currently present in the system library. If it is required, it can be set to any URL of the document. A unique glossary API built to set glossary, index and content. Uniquely here we used to google language library for to support multi-lingual. The UI is light weight and UI itself designed as an internal stub to create or retrieve data. In future it is easy to enable the voice input and entry points supports ANSI, ASCII, UNICODE and DBCS characters to support. The stopwords are the propositions or the vowels to avoid during the indexing of the words. The stemming has some unique methods to follow and to cut down the letters used.